2018
DOI: 10.18488/journal.1.2018.811.974.984
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Theoretical Framework for Understanding the Role of Structural Capability in Quality Management Practices on Quality Performance

Abstract: With the growing pressure to achieve optimum level of quality, quality management practices (QMPs) has gained greater attention in developing countries. However, the contradictory evidence shown in the existing QM literatures had raised doubts as to whether QMPs alone is sufficient to achieve promising quality performance. In this regard, this paper aims to address the importance of structural capability in the pursuit of successful QM implementation seeing as the absent of structural capability may impose cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…There is a need to facilitate the creation of wireless information infrastructures, and alleviate the digital divide resulting from differences in family income, educational attainment, occupation, employment status, race, gender, age and geography (Wang et al 2016). Ling, Jusoh and Ishak (2018) concluded that demographic variables such as income, education and age have a modest impact on the decision whether to buy online, whereas the most important determinant of online shopping was previous behaviour, such as earlier online purchases.…”
Section: Demographic Features Of Online Shoppersmentioning
confidence: 99%
“…There is a need to facilitate the creation of wireless information infrastructures, and alleviate the digital divide resulting from differences in family income, educational attainment, occupation, employment status, race, gender, age and geography (Wang et al 2016). Ling, Jusoh and Ishak (2018) concluded that demographic variables such as income, education and age have a modest impact on the decision whether to buy online, whereas the most important determinant of online shopping was previous behaviour, such as earlier online purchases.…”
Section: Demographic Features Of Online Shoppersmentioning
confidence: 99%
“…Lastly, the exempt supplies where business is not allowed to claim input tax credit when they bought the supplies. The business is also not eligible to impose output tax to their customer (Ling, Jusoh & Ishak 2018).…”
Section: Gstmentioning
confidence: 99%
“…Organizational culture is a core value for a system which consists of common values. Personal values begin to advance early in life and, like the more common beliefs, are systematized into hierarchical arrangements with measurable properties as well as apparent behavioural results (Douglas et al, 2001;Çevik & Özgünay, 2018;Azad et al, 2018;Koumje, 2018;Ling, et al, 2018). Personal values are central, or closer to one's personality as compared with other constructs like attitudes as well as opinions (Ravlin & Meglino, 1987) which are crucial in ethical culture.…”
Section: Organization Culture Ethicsmentioning
confidence: 99%